PENGEMBANGAN E-MODUL SEJARAH MATERI MASUKNYA AGAMA DAN KEBUDAYAAN HINDU-BUDDHA DI NUSANTARA UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS X TKJ 1 SMK AL-HUDA JATIMULYO - Ramadhani, Fadhilah (Universitas Indraprasta PGRI, 2023)
Abstract:The purpose of this study is (1) To produce a product in the form of an e-module in the history subject of class X SMK Al-Huda Jatimulyo with material on the entry of Hindu-Buddhist religion and culture in the archipelago. (2) Knowing the response of teachers and students to the development of the History e-module. (3) Improving student learning outcomes in History subjects through the use of electronic modules (e-modules). This research and development refers to the research steps of ADDIE. The test subject was class X TKJ 1 SMK Al-Huda Jatimulyo. Data collection uses questionnaires, observations and interviews. Data analysis using a Likert scale with 4 answers and an N-Gain Score test. The results of this study are in the form of (1) History learning resources in the form of E-Modules are suitable for use based on uji validation by 92% material experts, 96% media experts and 100% linguists with very valid criteria.( 2) Based on the teacher's response to the development of History learning resources in the form of E-modules at the time of the trial limited to 92.30%, and at the time of the broad trial 98.07% with very valid eligibility criteria. Based on student responses, History learning resources in the form of E-Modules at the time of the trial were limited to 84.61% and at the time of the broad trial 91.72% with very valid eligibility criteria. (3) The trial N-Gain score got a value of 0.62 belonging to the valid category. Based on the eligibility level criteria, learning resources in the form of electronic modules (E-modules) are included in valid qualifications, meaning that learning resources in the form of E-Module History can improve student learning outcomes.Keywords: Development, E-Module, Learning Outcomes